Cultural Safety Over Competence: A Paradigm Shift in Ethnopsychiatric Nursing Communication - Indi Dwi Shofi Yanti; Anggun Novia Indah Fitri; Fatma Lutfiyatus Sayyida (Interdisciplinary Journal of Ethnopsychiatric Nursing, 2025)
Effective communication in ethnopsychiatric nursing is essential for delivering equitable mental health care to culturally and linguistically diverse (CLD) populations. This study presents a systematic review of evidence-based communication strategies that enhance nurse-patient interactions in multicultural psychiatric settings, guided by the PRISMA framework. A comprehensive analysis of global studies reveals a multidimensional framework integrating professional interpretation, intercultural education, empathetic engagement, and institutional support as key components for improving clinical outcomes. Findings emphasize that accurate diagnosis, treatment adherence, and therapeutic trust are significantly enhanced through structured language access services and cultural competence training. Persistent barriers such as institutional underinvestment, limited policy enforcement, and challenges in adapting strategies to local sociocultural contexts were also identified. The review highlights the critical role of cultural humility, trauma-informed approaches, and collaborative care models in fostering inclusive and ethical mental health services. Recommendations include mandating interpreter services, embedding cultural safety into nursing curricula, expanding teleinterpreting options, promoting diverse clinical environments, and supporting context-specific training programs. Institutional reforms and multisectoral collaboration are necessary to ensure sustainable improvements in cross-cultural psychiatric care. By addressing systemic inequities and enhancing provider competencies, this research contributes to advancing culturally responsive psychiatry and achieving equitable mental health outcomes globally.